Nucleate flow boiling enhancement on engineered three-dimensional porous metallic structures in FC-72 - Wong, Kin Keong (2020)
Flow boiling heat transfer experiments were conducted in a closed-loop facility on engineered hollow structures using FC-72 as the working fluid. The use of Selective Laser Melting, an additive manufacturing technique, has allowed the fabrication of specialized 3D porous metallic structures with repeating unit cells of spherical voids and cylindrical connecting channels. Three porous substrates which consist of a small, large and gradient unit cells were fabricated. The porous substrates show superior flow boiling heat transfer as compared to a plain surface due to the increased number of nucleation sites and more vigorous flow mixing. For each substrate, the heat transfer coefficient shows an initial increasing trend from low to mid-range of the exit vapor quality and deteriorates thereafter when approaching the dry-out condition. Visualizations using a high-speed camera reveal that bubbly and churn flows were prevalent in the substrates and suggest the strong dominance of nucleate boiling over the convective mechanism. The Gradient-reverse substrate showed superior performance due to the channeling of the liquid-vapor mixture into smaller cross-sectional areas and the delay of dry-out for high vapor quality.